Dual Aromatase-Sulphatase Inhibitors (DASIs) for the Treatment of Hormone Dependent Breast Cancer - Banjare, Laxmi; Jain, Akhlesh K.; Thareja, Suresh (Mini Reviews in Medicinal Chemistry, 2021)
Abstract: Breast cancer is the most frequently diagnosed cancer in women and the second most common form of cancer, causing death after lung cancer, all across the globe at an alarming rate. The level of estrogens in breast cancer tissues of postmenopausal women is 10-40 folds higher than the non-carcinogenic breast tissues. As a result of this greater level of estrogen, breast tissue becomes more prone to develop breast cancer; mainly, estradiol plays a significant role in the initiation and development of hormone-dependent breast cancer. Androstenedione, Adrenal dehydroepiandrosterone sulfate, and estrone-sulfate also play an important role as precursors for estrogen biosynthesis. Estrogen deprivation exhibits an attractive phenomenon in the advancement of ideal therapeutics for the treatment of breast cancer. Inhibition of aromatase and sulphatase emerged as an attractive therapy for the treatment of hormone-dependent breast cancer via deprivation of estrogen by different pathways. The cocktail of aromatase and sulphatase inhibitors known as Dual Aromatase-sulphatase Inhibitors (DASIs) emerged as an attractive approach for effective estrogen deprivation. The present review article focused on the journey of dual aromatase-sulphatase inhibitors from the beginning to date (2020). Keeping in view the key observations, this review may be helpful for medicinal chemists to design and develop new and efficient dual aromatase-sulphatase inhibitors for the possible treatment of hormone- related breast cancer.
Keywords: dual inhibitors